KONSTRUKSI MAKNA MEDIA SOSIAL BAGI ANGGOTA DPRD KOTA PADANG - Sumartono (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2017)
This study aims to determine the construction of the meaning of social media for members of the Parliament of Padang Town. This research is done through a paradigm approach konstuktivis using phenomenology method. The focus of this research is political communication with research subjects of DPRD Padang 2014-2019 as many as 6 orang. Informant determination through the technique of data collection is done through indepth interview, observation, and documentation study. The result of the research shows that members of Parliament of Padang Town (2014-2019) interpret social media as media of media, media of presentation, and media of self-image. Social media as a medium of friendship means social media has functioned as a means of interaction, information, and publication of members of the council to the community or vice versa from society to board members. Social media has been used as a medium of direct communication or media interaction between politicians with the netizens. While the meaning of social media as a media presentation means social media to be a platform for members of the Parliament of Padang Town to demonstrate its existence as a representative of the people. While the meaning of social media as a medium of self-image is how the efforts of members council in the activities of strengthening its position as a representative of the people which is worthy of community support.